Comparison of Radiographic Femur Measurements in Stillbirths and Neonatal Deaths to Ultrasound Measurements in Ongoing Pregnancies. (March 2014) - Pinar, Halit; Palomaki, Glenn E.; Haddow, Hamish R. M.; Rowles, Andrew; Torabi, Ramyar
Identifying growth abnormalities in stillbirths is clinically useful but complicated by maceration. This is an observational study of consecutive postmortem examinations in which femur lengths and gestational age at delivery were collected, along with associated congenital anomalies and extent of fetal maceration. Between 2005 and 2012, 1530 consecutive postmortem examinations were performed and the information recorded. Fragmented fetuses (417), live-born fetuses that survived for more than 24 hours (134), fetuses with any signs of maceration (419), fetuses with known anomalies (98), and records with missing data (249) were excluded. The analyses focused on the remaining 265 nonmacerated stillborn fetuses and infants that survived for less than 24 hours after birth. The relationship between gestational age at delivery and femur length was computed, and a quadratic equation fit the data well between 12 and 40 weeks' gestation (R = 0.944). Gestational age–specific reference ranges for radiographic femur measurements in stillbirths are equivalent to those for ultrasound-determined measurements in ongoing pregnancies. These reference data may be useful in identifying growth abnormalities in nonmacerated stillborn fetuses.